The Effectiveness of Using the Differentiation-Based Wattpad Application in Teaching Intertextuality in Hikayat to Become Short Stories - Rahmah Diva Aprilia; Idhoofiyatul Fatin; Dian Karina Rachmawati (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Initial observations conducted on students of class X AKL-1 SMK Mudisa showed that there were difficulties faced by students in learning the intertext of hikayat into short stories. This was seen from the low student scores and supported by teacher validation which stated that students still had difficulty in developing stories, so that learning media that was close to students was needed, namely the Wattpad application. This study aims to describe the effectiveness of using the Wattpad application in the process of learning the intertext of hikayat into short stories which was also based on non-cognitive differentiation. This study applied an experimental method with a pre-experimental research type with one group pre-test post-test design. The subjects of this study were 21 students of class 10 AKL-2 SMK Mudisa. The data that can be summarized in the writing published on the Wattpad application, both initial test data and final test data. The data that has been obtained will then be analyzed using statistics according to the inferential statistical process, namely one sample test and paired samples statistics test through the SPSS application version 16.0 windows. This research obtained the following results: (1) the initial test conducted on students in the process of learning the intertext of fairy tales into short stories was in the less category with an average of 55.14; (2) the results of the final test of intertext of fairy tales into short stories were at an average of 88.40 after non-cognitive differentiation-based learning and the use of the Wattpad application; (3) a clear difference in the initial test results with a score of 55.14 increasing in the final test with a score of 88.40, so that the increase with an average of 33.76 proves that the use of the Wattpad application based on non-cognitive differentiation is effective in learning the intertext of fairy tales into short stories.